Assessing the Effect of Audit Quality on Agency Dynamics: Evidence in Kurdistan - Sardar Jalal Braim; Rebin Bilal Mohammed; Bryar Sami Abdulrahman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The study’s objective is to analyze how audit quality impacts the effectiveness of corporate governance mechanisms, the role of auditors in aligning the interests of shareholders and managers, and the reduction of the level of agency conflicts. The problem being that agency dynamics encompass the complex interactions and potential conflicts of interest that emerge when managers, acting as agents, make decisions on behalf of shareholders, who are the ultimate principals. 198 questionnaire responses were collected from accountants, auditors, finance managers and general managers of food and retail, banking, manufacturing, education and construction companies in Erbil city were analyzed using a single regression analysis approach. The results of the study demonstrated that improvements in audit quality significantly enhance the effectiveness of corporate governance mechanisms and the role of auditors in aligning the interests of shareholders and managers. Audit quality’s impact on the reduction of the level of agency conflicts was found to be insignificant. The study revealed positive effects spanning from audit quality, corporate governance mechanisms, auditors’ roles to improved agency dynamics in Kurdistan-based companies. Auditors and auditing firms should prioritize continuous improvement in audit quality, investing in professional development and adherence to international auditing standards. Moreover, companies in Kurdistan should adopt and promote robust corporate governance practices that align the interests of shareholders and managers. Regulatory bodies in Kurdistan should consider reviewing and updating the regulatory framework governing audit quality and corporate governance to ensure alignment with best practices and international standards